Upaya Meningkatkan Kemampuan Menulis Tegak Bersambung Melalui Contoh di Buku Halus dan Drill pada Peserta Didik Kelas I SDN Jajartunggal III Surabaya - WIDYANINGRUM, RIZKY (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
This study aims to improve students' writing skills through the application of sampling and drill techniques to student participants. This technique is one form of developing skills learning found in four aspects of Indonesian language learning by combining letter by letter, thus forming a word and sentence. The type of research conducted is Class Action Research. The subjects of this study were first grade students of Jajartunggal III Surabaya Elementary School. This research was preceded by preliminary observations, followed by planning learning, implementation, observation per cycle and ending with evaluation. The activity is carried out with 2 cycles, with the hope that students' upright writing skills will increase. The results of upright writing learning through the model of giving examples in notebooks and drills to class I students are characterized by an increase in the average value of student. The average value of students in pre-action activities with an increase of 60. The condition experienced an increase in the average value of students in cycle 1 which is equal to 75 and the percentage of completeness by 55%. However, this increase has not yet reached the target set previously. Then after proceeding to 2nd cycle the average value in recurring writing learning increased by 81.2 with a percentage of completeness of 84%. This shows that the previously set target has been reached so that the research is stopped in 2nd cycle.